THE OCCURRENCE DURING ACUTE INFECTIONS OF A PROTEIN NOT NORMALLY PRESENT IN THE BLOOD : V. PHYSICAL-CHEMICAL PROPERTIES OF THE C-REACTIVE PROTEIN CRYSTALLIZED BY A MODIFIED TECHNIQUE - Wood, Harrison F. (The Rockefeller University Press, 1954)
A method is described for obtaining crystalline C-reactive protein from serous fluids in which the protein is associated with lipid. Most pathological fluids currently available as a source of this protein appear to fall in this category. Crystalline C-reactive protein has its isoelectric point at pH 4.82 as determined by free electrophoresis in McIlvaine's buffer. Its mobility in the electrophoresis cell, both alone and after addition to normal serum, coincides with that of the β-globulin fraction of the serum. In contrast to this finding, by the method of zone electrophoresis on a starch supporting medium the protein migrates with the γ(1)-globulin. The significance of this discrepancy is discussed. Studies in the ultracentrifuge indicate an s (20,w) of 7.5.